Kinetika Reaksi Sintesis Hidroksiapatit Dari Tulang Sapi Dengan Metode Presipitasi - Deni Astika; Ahmad Fadli; Silvia Reni Yenty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite is one of kind bioceramics that can be use for implant in human body. Bioceramics hydroxyapatite was synthesized from bovine bones by using precipitation method. The purpose of this research was to determine the influence of temperature reaction to reduction concentration of calcium hydroxide and then to determine the kinetics reaction of synthesis hydroxiapatite from bovine bones by using precipitation method. Bovine bones was calcined at temperatures 1000℃ to produce calcium oxide (CaO). CaO was dissolved to distilled water and was mixed gently in to phosphoric acid (H3PO4) and then was heated. Then the filtrate tested by using complexometry to gain the concentration of calcium hydroxide. The result of kinetics reaction in synthesis hydroxiapatite from bovine bones by using precipitation method can by approaching to pseudo first order equations and pseudo second order. The reaction rate constants by using variation temperature can be approximated by using Arrhenius equation by value obtained are :k = 82,43e- (25382.64 / RT)Keywords : hydroxyapatite, precipitation, reaction kinetics, pseudo first order